Strategi Pemasaran Waktu Malam pada Usaha Martabak: Analisis Pendekatan Psikologis dan Ekonomi (Jurnal Manajemen Bisnis Digital Terkini, 2026)
This qualitative inquiry examines the deliberate operational timing adopted by street vendors selling martabak, a popular Indonesian snack, exploring why nocturnal hours are strategically favored over daytime. The research methodology combined in-depth interviews with ten vendors operating in urban centers like Jakarta and Bandung with a consumer survey of one hundred respondents. Analysis of the collected data identifies a dual strategic foundation. From a demand perspective, night-time aligns with consumer psychology, fostering a leisurely atmosphere conducive to social snacking and impulsive purchases. On the supply side, vendors benefit from diminished direct competition, reduced operational overheads, and tapping into peak demand for evening treats. This synergy effectively cements martabak’s market identity as a beloved night-time culinary ritual linked to socialization. Consequently, the study posits that this chrono-marketing approach represents a savvy adaptation to local socio-economic rhythms. The insights derived provide a framework for micro-entrepreneurs to optimize service timing, aligning business operations with ingrained cultural consumption cycles to enhance sustainability and customer loyalty.